Implementasi Himbauan Kementerian Agama Tentang Syarat Pendaftaran Nikah Perspektif Hukum Islam Dan Hukum Positif Di Kabupaten Bengkulu Selatan - Apriansyah, Rio (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2024)
Abstract: "Implementation of the appeal of the Ministry of Religion in South Bengkulu district regarding the requirements for marriage registration from the perspective of Islamic law and positive law." an appeal from the South Bengkulu Ministry of Religion regarding the requirements for marriage registration? (2) What is the review of Islamic law and positive law on the implementation of the South Bengkulu Ministry of Religion's appeal regarding the requirements for marriage registration. The research method used in this research is field research, namely collecting data directly in the field. The research location to be taken is the Ministry of Religion of South Bengkulu Regency. while for the research informants, namely the Ministry of Religion, Head of Section for Islamic Community Guidance, Head of Section for Islamic Community Guidance, Sharia Organizers, Head of KUA and the people of South Bengkulu. This data collection technique uses interviews and documentation. The results of the research conducted were the implementation of the appeal from the South Bengkulu Ministry of Religion regarding the requirements for marriage registration, namely requiring parents' marriage books as a requirement for marriage at the South Bengkulu KUA, realized by the KUA by writing it on the marriage registration form. Based on this call from the Ministry of Religion, there are still differences in implementation between KUA heads, such as some requiring only the first daughter and others requiring all daughters. Although the goal is the same, namely to determine the guardian of marriage. Then if viewed from the positive law regarding the parents' marriage book which is determined to be an administrative requirement for marriage, it is still classified as having very weak legal force because there are no written regulations that form the basis of the appeal, and only based on MUI fatwa No. 11 of 2012 concerning the status of children resulting from adultery and their treatment.Keywords: Ministry of Religion, Marriage Requirements, Islamic Law, Positive Law Abstrak: “Implementasi himbauan Kementrian Agama di kabupaten Bengkulu Selatan tentang syarat pendaftaran nikah perspektif hukum Islam dan hukum positif” Dalam hal ini persoalan yang akan di bahas pada tesis, yaitu: (1) Bagaimana implementasi himbauan Kementerian Agama Bengkulu Selatan tentang syarat pendaftaran nikah? (2) Bagaimana tinjauan hukum Islam dan hukum positif terhadap implementasi himbauan kementerian Agama Bengkulu Selatan tentang syarat pendaftaran nikah. Adapun metode penelitian yang digunakan dalam penelitian ini adalah penelitian lapangan (field research) yaitu pengumpulan data secara langsung dilapangan. Lokasi penelitian yang akan di ambil yaitu Kementerian Agama Kabupaten Bengkulu Selatan. sedangkan untuk informan penelitian yaitu Kementrian Agama, Kepala Kasi Bimas Islam, Staf Kasi Bimas Islam, Penyelenggara Syariah, Kepala KUA dan masyarakat Bengkulu Selatan.Teknikpengumpulan data ini menggunakan wawancara dan dokumentasi. Hasil dari penelitian yang dilakukan yaitu Implementasi himbauan Kementerian Agama Bengkulu Selatan tentang syarat pendaftaran nikah yaitu mewajibkan buku nikah orangtua sebagai persyaratan nikah yang ada di KUA Bengkulu Selatan, diwujudkan oleh KUA dengan menuliskannya di formulir pendaftran nikah. Berdasarkan himbauan Kementerian Agama ini, masih terjadi perbedaan penerapan di antara kepala KUA, seperti ada yang mewajibkan untuk anak perempuan pertama saja dan ada juga yang mewajibkan untuk semua anak perempuan. Meskipun tujuannya sama yaitu untuk menentukan wali nikah. Kemudian jika ditinjau dari hukum positif mengenai buku nikah orangtua yang ditetapkan menjadi persyaratan administratif pernikahan, masih tergolong sangat lemah  kekuatan hukumnya karena tidak ada peraturan tertulis yang menjadi dasar himbauan tersebut, dan hanya berdasarkan fatwa MUI No. 11 Tahun 2012 tentang kedudukan anak hasil zina dan perlakuan terhadapnya.Kata kunci:  Kementerian Agama, Persyaratan Nikah, Hukum Islam, Hukum Positif.